Sodium ion battery modified positive electrode based on boron salt structure regulation and application thereof

CN122889679APending Publication Date: 2026-10-09SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611012840.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,现有界面调控方法普遍存在制备工艺复杂、成本较高、适配性有限等问题;同时,现有成膜添加剂大多以电解液添加形式使用,存在添加量受限、界面分布不均匀以及界面稳定效果有限等缺陷,无法长期维持稳定有效的界面保护效果

Benefits of technology

(1)本发明通过在正极体系中引入含硼盐功能添加剂,利用其特有的结构特性、多阴离子结构单元及优异的化学稳定性,使其能够以固相形式稳定存在于正极体系中,并持续调控正极/电解液界面反应过程,有效降低界面副反应程度,改善正极界面稳定性。与传统电解液添加剂依赖溶解分散和界面成膜的作用方式相比,本发明所述功能添加剂具有更加稳定持久的界面调控能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889679A_ABST
    Figure CN122889679A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of sodium ion batteries, and particularly relates to a modified positive electrode of a sodium ion battery based on structure regulation of boron salt and application thereof. By introducing a boron salt functional additive into the positive electrode system, the application realizes interface regulation, the additive can regulate the positive electrode-electrolyte interface reaction by virtue of a special structure, multiple anion units and excellent chemical stability, simultaneously realizes electrode interface regulation and transition metal ion fixation, inhibits positive electrode structure degradation and transition metal dissolution in the cycle process, and significantly improves the cycle stability, capacity retention rate and rate performance of the battery. Meanwhile, the application does not need to perform complex modification such as doping and coating on the positive electrode active material, and can take effect by adding a small amount of boron salt, and the process is simple, the cost is low, and the production is easy to scale. In addition, the boron salt additive can be compatible with existing electrode preparation processes such as wet coating and dry film forming at the same time, the material has good universality and process adaptability, and has good industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a modified cathode for sodium-ion batteries based on boron salt structure regulation and its application. Background Technology

[0002] Sodium-ion batteries are considered an important supplement and potential alternative to lithium-ion batteries due to their advantages such as abundant sodium resources, low cost, excellent low-temperature performance, high safety, and suitability for large-scale energy storage. Currently, the cathode materials for sodium-ion batteries mainly include layered oxide materials, Prussian blue analogues, and polyanionic materials. Layered oxide materials mainly include nickel-iron-manganese oxides and copper-iron-manganese oxides; Prussian blue analogues mainly include iron-based Prussian blue and manganese-based Prussian white; and polyanionic materials mainly include sodium iron sulfate, sodium iron phosphate, and sodium iron pyrophosphate. Although these material systems each have advantages in energy density, rate performance, and cost, they all generally suffer from varying degrees of transition metal dissolution during charge-discharge cycles.

[0003] The problem of transition metal dissolution is mainly attributed to the insufficient stability of the lattice structure of the cathode material and the corrosive effect of the electrolyte on the cathode surface. On the one hand, the cathode material is prone to local structural collapse, metal-anion bond breakage, and interfacial side reactions during high-voltage cycling, causing transition metal ions to be released from the main structure. On the other hand, the electrolyte is prone to oxidative decomposition under high-potential conditions, generating acidic or active byproducts that continuously corrode the cathode surface, further aggravating the dissolution of transition metal ions. After the dissolved transition metal ions migrate to the anode, they also disrupt the stability of the anode interfacial film, leading to continuous consumption of active sodium, increased interfacial impedance, and ultimately resulting in battery capacity decay, decreased rate performance, and shortened cycle life.

[0004] To address these issues, existing technologies typically employ strategies such as elemental doping, surface coating, electrolyte optimization, and additive regulation to enhance the structural and interfacial stability of cathode materials. Among these, constructing a stable cathode-electrolyte interphase (CEI) film to isolate the cathode material from direct contact with the electrolyte is considered a crucial means of suppressing transition metal dissolution and reducing interfacial side reactions. However, existing interfacial regulation methods generally suffer from complex preparation processes, high costs, and limited adaptability. Furthermore, most existing film-forming additives are used in the form of electrolyte additions, which have drawbacks such as limited addition amounts, uneven interfacial distribution, and limited interfacial stabilization effects, failing to maintain a stable and effective interfacial protection effect over the long term.

[0005] Furthermore, existing technologies primarily focus on reducing the dissolution rate of transition metal ions, while paying insufficient attention to the further treatment of already dissolved transition metal ions. In fact, transition metal ions that have already entered the electrolyte may continue to participate in interfacial side reactions and migrate and deposit towards the negative electrode, thereby accelerating battery performance degradation. Therefore, if it is possible to effectively immobilize, adsorb, or restrict the migration of already dissolved transition metal ions while suppressing their dissolution, it is expected to further reduce their adverse effects on the battery system and improve the long-term cycle stability of the battery.

[0006] In summary, there is an urgent need to develop a novel functional additive that is compatible with existing sodium-ion battery manufacturing processes and also has the functions of interface regulation and transition metal ion immobilization. This would effectively regulate the cathode / electrolyte interface reaction process, reduce transition metal dissolution, and inhibit the migration and accumulation of dissolved metal ions, thereby improving the cycle stability and overall electrochemical performance of sodium-ion batteries. Summary of the Invention

[0007] To overcome the shortcomings of the prior art, this invention provides a modified cathode for sodium-ion batteries based on boron salt structure regulation. By introducing boron salt functional additives into the cathode system, and utilizing their unique spatial structure, multi-anion structural units, and excellent chemical stability, it is possible to simultaneously achieve electrode interface regulation and transition metal ion fixation. Furthermore, this modified cathode is compatible with existing sodium-ion battery manufacturing processes, effectively balancing process compatibility and electrochemical performance optimization.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a modified cathode for sodium-ion batteries. The modified cathode comprises a cathode active material, a conductive agent, a binder, and a functional additive. The functional additive is one or more boron-containing salt compounds. The cations in the boron-containing salt compounds include sodium ions, lithium ions, and potassium ions (the cations in the boron-containing salt compounds are not limited to sodium ions, but may also include lithium ions, potassium ions, or other alkali metal ions. The cations are mainly used to maintain the structural stability and chemical composition of the compound, rather than participating in electrochemical energy storage reactions as decisive functional components. The boron-containing salt compounds are poorly soluble in the electrolyte during electrochemical cycling and can exist stably in the cathode system in solid form. Their functional role mainly comes from their own structural characteristics and their interaction with the cathode interface and transition metal ions). When the modified positive electrode is loaded onto a positive electrode current collector to prepare a positive electrode sheet, the modified positive electrode can be adapted to both wet and dry preparation processes.

[0009] Preferably, the functional additive includes one or more of lithium tetrafluoroborate (LiBF4), sodium tetrafluoroborate (NaBF4), lithium tetrafluoroborate (Li2B4O7), potassium tetrafluoroborate (KBF4), cesium tetrafluoroborate (CsBF4), magnesium tetrafluoroborate (Mg(BF4)2), calcium tetrafluoroborate (Ca(BF4)2), aluminum tetrafluoroborate (Al(BF4)3), sodium tetrafluoroborate (Na2B4O7), potassium tetrafluoroborate (K2B4O7), calcium tetrafluoroborate (CaB4O7), magnesium tetrafluoroborate (MgB4O7), and aluminum tetrafluoroborate (Al4B2O9).

[0010] The improvement in cathode interface stability by the boron-containing salt compound primarily stems from its unique structural characteristics, rather than solely relying on the introduction of boron. Specifically, the boron-containing salt compound possesses a stable localized coordination structure, multiple anion structural units, and strong chemical stability. During electrochemical cycling, it can regulate the cathode / electrolyte interface reaction process, reduce the degree of interfacial side reactions, and promote the formation of a structurally stable interfacial protective layer, thereby slowing down the structural degradation of the cathode material and the dissolution of transition metals. Simultaneously, the boron-containing salt compound can immobilize transition metal ions in the electrolyte, reducing their migration ability and interfacial reactivity, thereby minimizing the deposition of transition metal ions on the anode surface and the side reactions they trigger.

[0011] By adjusting the composition ratio of functional additives to cathode active materials, the stability of the cathode interface, the dissolution behavior of transition metals, and the electrochemical performance can be optimized. Preferably, in the modified cathode, the mass ratio of cathode active material, conductive agent, and binder is 60–98:0.01–30:1–20, and the amount of functional additives added is 0.01 wt.%–30 wt.% of the total mass of cathode active materials, preferably 1 wt.%–10 wt.%.

[0012] Preferably, the positive electrode active material includes (but is not limited to) one or more of layered oxide materials, Prussian blue analog materials, and polyanionic materials.

[0013] More preferably, the layered oxide material includes one or more of nickel-iron-manganese oxide and copper-iron-manganese oxide; the Prussian blue analog material includes one or more of iron-based Prussian blue and manganese-based Prussian white; and the polyanionic material includes one or more of sodium ferric sulfate, sodium ferric phosphate, sodium ferric pyrophosphate, and sodium vanadium pyrophosphate.

[0014] Preferably, the conductive agent includes (but is not limited to) one or more of conductive carbon black, acetylene black, Ketjen black, multi-walled carbon nanotubes, carbon nanofibers, conductive graphite, graphene, and reduced graphene oxide. The carbon nanofibers include vapor-grown carbon fibers (VGCF), and the conductive graphite includes one or more of KS-6, KS-15, SFG-6, and SFG-15.

[0015] More preferably, the adhesive includes (but is not limited to) one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium alginate (SA), and polytetrafluoroethylene (PTFE).

[0016] Preferably, the adhesive is polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE).

[0017] Preferably, the wet preparation process includes one or more of slurry dispersion, coating, drying and rolling, and the dry preparation process includes one or more of mechanical mixing, fiberization and rolling film formation.

[0018] Preferably, the positive electrode current collector used in the wet preparation process includes (but is not limited to) one or more of aluminum foil, coated aluminum foil, foamed aluminum, and perforated aluminum foil, with aluminum foil being the most preferred; the positive electrode current collector used in the dry preparation process includes (but is not limited to) stainless steel mesh and titanium mesh, with stainless steel mesh being the most preferred.

[0019] Preferably, the functional additive can be pre-mixed with the positive electrode active material and then mixed with the conductive agent and binder to prepare the modified positive electrode; or, the positive electrode active material, conductive agent, binder and functional additive can be added sequentially or simultaneously and mixed evenly to obtain the modified positive electrode.

[0020] The second aspect of the present invention also provides the application of the modified cathode described in the first aspect in the preparation of sodium-ion batteries.

[0021] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention introduces boron-containing functional additives into the cathode system. Utilizing their unique structural characteristics, multi-anionic structural units, and excellent chemical stability, these additives can exist stably in the cathode system in a solid phase and continuously regulate the cathode / electrolyte interface reaction process, effectively reducing the degree of interfacial side reactions and improving the cathode interface stability. Compared with traditional electrolyte additives that rely on dissolution, dispersion, and interfacial film formation, the functional additives described in this invention have a more stable and lasting interfacial regulation capability.

[0022] (2) The boron-containing functional additives used in this invention can not only slow down the structural degradation of the positive electrode material and the dissolution of transition metals during the cycling process, but also effectively fix the dissolved transition metal ions, reduce their accumulation in the electrolyte and the interfacial side reactions caused by their migration and deposition to the negative electrode side.

[0023] (3) The boron salt functional additives described in this invention are applicable to various sodium-ion battery cathode systems such as layered oxide materials, Prussian blue analog materials and polyanionic materials. They have good material compatibility and versatility and can be widely used in the stabilization and regulation of different types of sodium-ion battery cathodes.

[0024] (4) The present invention does not require complex doping, surface coating or structural modification of the positive electrode active material body. It can improve the stability of the positive electrode by introducing a small amount of functional additives. It has the advantages of simple process, convenient implementation, low cost and easy large-scale preparation.

[0025] (5) The modified cathode of sodium-ion battery based on boron salt structure regulation provided by the present invention is applicable to both wet coating process and dry electrode process, and can be compatible with the existing sodium-ion battery manufacturing process, with good process adaptability and industrial application prospects. Attached Figure Description

[0026] Figure 1 The cycle retention rate of the sodium-ion half-cells in Example 1 and Comparative Example 1; Figure 2 The image shows a scanning electron microscope image of the positive electrode sheet in Comparative Example 1 without the addition of boron salt functional additives after one charge-discharge cycle at 0.1C. Figure 3 This is a scanning electron microscope image of the positive electrode sheet with boron salt functional additive added in Example 1 after one charge-discharge cycle at 0.1C. Detailed Implementation

[0027] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0028] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0029] Example 1: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel-iron-manganese oxide (NFM; CAS No.: 1307699-76-8), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and lithium tetrafluoroborate (LiBF4) was added as a functional additive at a mass ratio of 1 wt.% of the positive electrode active material. After uniformly mixing the above components, an equal mass of N-methylpyrrolidone (NMP) was added as a dispersion medium for dispersion and homogenization to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector (approximately 16 μM thick and 195 mM wide) (coating thickness approximately 300 μM), dried in a vacuum oven at 100 ℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0030] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0031] Example 2: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel iron manganese oxide (NFM), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and lithium tetrafluoroborate (LiBF4) was added as a functional additive at a mass ratio of 5 wt.% of the positive electrode active material. After uniformly mixing the above components, the mixture was dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector, dried in a vacuum oven at 100℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0032] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0033] Example 3: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel-iron-manganese oxide (NFM), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and lithium tetrafluoroborate (LiBF4) was added as a functional additive at a mass ratio of 10 wt.% of the positive electrode active material. After uniformly mixing the above components, the mixture was dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector, dried in a vacuum oven at 100℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0034] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0035] Example 4: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel-iron-manganese oxide (NFM), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and lithium tetraborate (Li2B4O7) was added as a functional additive at a mass ratio of 1 wt.% of the positive electrode active material. After uniformly mixing the above components, the mixture was dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector, dried in a vacuum oven at 100℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0036] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0037] Example 5: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel-iron-manganese oxide (NFM), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and lithium tetraborate (Li2B4O7) was added as a functional additive at a mass ratio of 5 wt.% of the positive electrode active material. After uniformly mixing the above components, the mixture was dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector, dried in a vacuum oven at 100℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0038] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0039] Example 6: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel-iron-manganese oxide (NFM), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and lithium tetraborate (Li2B4O7) was added as a functional additive at a mass ratio of 10 wt.% of the positive electrode active material. After uniformly mixing the above components, the mixture was dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector, dried in a vacuum oven at 100℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0040] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0041] Example 7: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel-iron-manganese oxide (NFM), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and sodium tetrafluoroborate (NaBF4) was added as a functional additive at a mass ratio of 5 wt.% of the positive electrode active material. After uniformly mixing the above components, the mixture was dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector, dried in a vacuum oven at 100℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0042] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0043] Example 8: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Sodium ferric sulfate (NFS), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10, and lithium tetrafluoroborate (LiBF4) was added as a functional additive at a mass ratio of 5 wt.% of the positive electrode active material. After uniformly mixing the above components, the mixture was dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector, dried in a vacuum oven at 100℃ for 8 h, and then rolled and punched to obtain a modified positive electrode sheet.

[0044] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0045] Example 9: This embodiment provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Manganese-based Prussian white (MnHCF), conductive agent, and binder polytetrafluoroethylene (PTFE) were weighed in a mass ratio of 70:20:10, wherein the conductive agent was a mixture of Ketjen Black and Super P in equal mass. Lithium tetrafluoroborate (LiBF4) was further added as a functional additive, accounting for 5 wt.% of the mass of the positive electrode active material. The above components were thoroughly mechanically mixed, and the polytetrafluoroethylene was fibroinated during continuous rolling (at this time, hardening and smoothing can be observed), thereby forming a dry electrode film with a continuous conductive network and mechanical support structure. Subsequently, the obtained electrode film was pressed onto the surface of a stainless steel mesh current collector and dried in a vacuum oven at 100 ℃ for 8 h to obtain the modified positive electrode sheet.

[0046] (2) Sodium-ion battery assembly: Using the prepared modified positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin-type sodium-ion batteries were assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0047] Comparative Example 1: This comparative example provides a sodium-ion battery positive electrode and a sodium-ion battery assembled using the positive electrode. The preparation steps are as follows: (1) Preparation of positive electrode sheet: Nickel-iron-manganese oxide (NFM), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 80:10:10. After uniformly mixing the above components, they were dispersed and homogenized using N-methylpyrrolidone (NMP) as the dispersion medium to obtain a uniform positive electrode slurry. Subsequently, the obtained slurry was uniformly coated on the surface of an aluminum foil current collector and dried in a vacuum oven at 100 °C for 8 h. After that, it was rolled and punched to obtain a modified positive electrode sheet.

[0048] (2) Sodium-ion battery assembly: Using the prepared positive electrode as the positive electrode, metallic sodium as the negative electrode, and glass fiber membrane as the separator, CR2032 coin cell sodium-ion battery was assembled in an argon atmosphere glove box using 1 M NaClO4 / PC + 5 vol.% FEC as the electrolyte.

[0049] Experimental Example: Electrochemical Testing The batteries assembled in Examples 1-9 and Comparative Example 1 were subjected to constant current charge-discharge tests, with a test voltage range of 2.0-4.5 V. Specifically, the voltage range for the nickel-iron-manganese oxide (NFM) system was 2.0-4.25 V, the voltage range for the polyanionic cathode sodium iron sulfate (NFS) system was 2.0-4.5 V, and the electrode range for the Prussian blue analog cathode manganese-based Prussian white (MnHCF) system was 2.0-4.2 V. This was to evaluate the effect of functional additives on the cycle stability and electrochemical performance of the batteries.

[0050] Table 1 presents the electrochemical performance test results of the sodium-ion half-cells assembled in each embodiment and comparative example. As can be seen from Table 1, the batteries all exhibited excellent cycle stability after introducing boron-containing functional additives into the cathode system.

[0051] Taking the nickel-iron-manganese oxide (NFM) system as an example, Examples 1 through 7 all exhibited superior cycle performance compared to Comparative Example 1. With variations in the type and amount of additives, the battery's initial capacity, initial coulombic efficiency, and cycle stability all showed certain differences, indicating that boron-containing functional additives have a significant regulatory effect on the electrode interface. In particular, adding an appropriate amount of functional additives can better balance capacity utilization and long-term cycle stability.

[0052] In addition to lithium tetrafluoroborate (LiBF4) in Examples 1 to 3 and Examples 8 and 9, Examples 4 to 6, which use lithium tetrafluoroborate (Li2B4O7) as a functional additive, and Example 7, which uses sodium tetrafluoroborate (NaBF4) as a functional additive, also exhibit excellent cycling performance. This shows that the technical solution described in this invention is not limited to a single boron-containing salt compound, but is applicable to a variety of boron-containing salt systems and has good universality and applicability.

[0053] Furthermore, the present invention also demonstrates good applicability in the polyanionic positive electrode sodium ferric sulfate (NFS) system of Example 8 and the Prussian blue analog positive electrode manganese-based Prussian white (MnHCF) system of Example 9. In particular, the MnHCF system, which uses a dry electrode process to prepare the positive electrode sheet, further verifies that the boron-containing functional additives described in this invention are not only suitable for traditional wet coating processes, but also compatible with dry electrode processes, exhibiting good process adaptability and industrial application potential.

[0054] Table 1: Electrochemical test results of different sodium-ion batteries To further verify the effect of the boron-containing functional additive of the present invention on improving the cycle stability of sodium-ion batteries, long-cycle capacity retention curves were tested using Example 1 and Comparative Example 1 as examples, as shown below. Figure 1 As shown. By Figure 1It can be seen that in the initial stage of cycling, both Example 1 and Comparative Example 1 exhibited high capacity retention. However, as cycling progressed, the capacity decay of Comparative Example 1 gradually intensified, especially after approximately 220 cycles, showing a significant rapid decay; in contrast, Example 1 maintained a relatively gradual capacity decay trend throughout. After 300 cycles, the capacity retention of Example 1 remained at 67.9%, while that of Comparative Example 1 was only 38.5%. These results demonstrate that the boron-containing functional additive described in this invention can significantly improve the long-term cycling stability of the cathode material and effectively suppress the performance degradation of the electrode during long-term cycling.

[0055] To further investigate the state of boron-containing functional additives in the electrodes, using Example 1 and Comparative Example 1 as examples, two types of positive electrodes, one without functional additives and the other with functional additives, were subjected to a single charge-discharge cycle at 0.1C. The morphology was then characterized using scanning electron microscopy (SEM). The test results are as follows: Figure 2 , Figure 3 As shown. By Figure 2 It can be seen that the surface of the positive electrode without added functional additives is mainly composed of positive electrode active particles, and no obvious second-phase particles were observed. However, from... Figure 3 It can be observed that after one charge-discharge cycle, functional additive particles distributed among the positive electrode particles can still be clearly observed on the electrode surface. Their morphological characteristics have not changed significantly compared with those before the cycle, indicating that the boron-containing functional additive can maintain good structural stability during electrochemical cycling and can continue to exist in the positive electrode system in solid form.

[0056] Figure 2 , Figure 3 The characterization results combined Figure 1 The electrochemical performance results shown demonstrate that the boron-containing functional additive of this invention does not primarily rely on dissolving in the electrolyte to participate in interfacial reactions, but rather on its own stable structural characteristics to continuously exert its effects. This functional additive can effectively regulate the cathode / electrolyte interfacial reaction process, reduce the degree of interfacial side reactions, and slow down the structural degradation of the cathode material and the dissolution of transition metals. Simultaneously, it can also fix or restrict the migration of dissolved transition metal ions, thereby reducing their accumulation in the electrolyte and the side reactions caused by their migration to the anode side, ultimately improving the cycle stability and overall electrochemical performance of the sodium-ion battery.

[0057] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A modified positive electrode for sodium-ion batteries, characterized in that, The modified cathode includes a cathode active material, a conductive agent, a binder, and a functional additive. The functional additive is one or more boron-containing salt compounds, and the cations in the boron-containing salt compounds include sodium ions, lithium ions, and potassium ions. When the modified positive electrode is loaded onto a positive electrode current collector to prepare a positive electrode sheet, the modified positive electrode can be adapted to both wet and dry preparation processes.

2. The modified positive electrode for a sodium-ion battery according to claim 1, characterized in that, The functional additives include one or more of lithium tetrafluoroborate, sodium tetrafluoroborate, lithium tetraborate, potassium tetrafluoroborate, cesium tetrafluoroborate, magnesium tetrafluoroborate, calcium tetrafluoroborate, aluminum tetrafluoroborate, sodium tetraborate, potassium tetraborate, calcium tetraborate, magnesium tetraborate, and aluminum tetraborate.

3. The modified positive electrode for a sodium-ion battery according to claim 1, characterized in that, In the modified positive electrode, the mass ratio of positive electrode active material, conductive agent and binder is 60-98:0.01-30:1-20, and the amount of functional additive added is 0.01 wt.% to 30 wt.% of the mass of positive electrode active material.

4. The modified positive electrode for a sodium-ion battery according to claim 1, characterized in that, The positive electrode active material includes one or more of layered oxide materials, Prussian blue analog materials, and polyanionic materials.

5. The modified positive electrode for a sodium-ion battery according to claim 1, characterized in that, The conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, multi-walled carbon nanotubes, carbon nanofibers, conductive graphite, graphene, and reduced graphene oxide.

6. The modified positive electrode for a sodium-ion battery according to claim 1, characterized in that, The adhesive includes one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, sodium alginate, and polytetrafluoroethylene.

7. A modified positive electrode for a sodium-ion battery according to claim 1, characterized in that, The wet preparation process includes one or more of slurry dispersion, coating, drying and rolling, and the dry preparation process includes one or more of mechanical mixing, fiberization and rolling film formation.

8. A modified positive electrode for sodium-ion batteries according to claim 1, characterized in that, The positive electrode current collector used in the wet preparation process includes one or more of aluminum foil, coated aluminum foil, aluminum foam, and perforated aluminum foil; the positive electrode current collector used in the dry preparation process includes stainless steel mesh and titanium mesh.

9. A modified positive electrode for sodium-ion batteries according to any one of claims 1 to 8, characterized in that, The functional additive can be pre-mixed with the positive electrode active material and then mixed with the conductive agent and binder to prepare a modified positive electrode; or, the positive electrode active material, conductive agent, binder and functional additive can be added sequentially or simultaneously and mixed evenly to obtain a modified positive electrode.

10. The application of the modified cathode according to any one of claims 1 to 9 in the preparation of sodium-ion batteries.